Assessment of China’s Macro-Readiness for Integrated Innovative Management Technologies Employment - Guo, Xiaoqing; Chmutova, Iryna; Sochynska-Sybirtseva, Iryna; Karpunina, Maryna (Dr. Viktor Koval, 2023)
Introduction. Economic entities should constantly apply various forms of innovation, including managerial and organizational innovations, to ensure the processes of developing and acquiring adaptive capacity. One of these innovations is integrated management technologies covering several interacting heterogeneous technological, economic, organizational, social, and psychological processes or several management functions. Aim and tasks. The study aims to elaborate a procedure for assessing a country’s macro-readiness to apply integrated innovative management technologies and qualitatively characterise its level. Results. An assessment of macro-readiness to apply integrated innovative management technologies was conducted using the case of China. In order to obtain a generalized evaluation of the country’s macro-readiness to apply integrated innovative management technologies, synthetic taxonomic indicators based on readiness components and a general synthetic indicator were generated. The synthetic human capital and research indicator changed from low (0.243) in 2016 to high (0.647) in 2020. The same trend is inherent in the synthetic indicator of ICT availability and use, which increased from 0.367 to 0.920, and in the synthetic indicator of institutional and business environment, which increased from 0.310 to 0.876. Although it has improved from 0.205 to 0.451, the synthetic indicators of financial resources and development have not yet reached a high level. Conclusion. The suggested procedure for assessing macro-readiness to apply integrated innovative management technologies is based on constructing a synthetic indicator of readiness, combining the taxonomic indicators of human, digital, financial, and institutional readiness. This procedure, implying the determination of their qualitative levels, enables us to determine a country’s readiness to support business entities’ adoption of new management technologies. The assessment of China's readiness for applying integrated innovative management technologies using the developed approach revealed that the ICT component is the best developed, while the financial component is the most underdeveloped.